An exploratory study of visitors' motivations at a heritage destination: The case of the South Luogu Alley in China. Issue 2 (3rd June 2019) - Shi, Xiaolin; Day, Jonathon; Gordon, Susan; Cai, Liping; Adler, Howard
Abstract : Purpose: The purpose of this paper is to examine visitors' motivations for going to the South Luogu Alley, a famous hutong with an over 700-year history in Beijing, China. Design/methodology/approach: The study applied a self-administered questionnaire to collect data from visitors on the main street of the South Luogu Alley. Findings: It was found that most visitors of the hutong are casual tourists pursuing relaxation, including tension release and spending time with friends and family; seeking authenticity is not visitors' most important motivation. Research limitations/implications: This study used only one hutong to assess visitors' motivations in hutong tourism, so the results may not be applicable to all hutongs. Practical implications: The research on the demographics and different motivations of the South Luogu Alley visitors can be useful to managers of tourism-related organizations. Social implications: This study shows that tourists with different motivations for visiting a hutong have varying requirements for authenticity. The reconstruction of some historical hutongs is not always perceived as negative, and the influence of Western cultural elements can be seen as positive if they contribute to the sustainable development of the local culture. Originality/value: The term "hutonger, " which includes casual visitors, entertainment seekers, authenticity seekers and pure escapees, based on these respective motivations, is introduced to describe the specific groups of hutong visitors and contribute to the hutong tourism literature.